Las actividades físicas recreativas y la calidad de vida del adulto mayor, de la parroquia Urdaneta, cantón Saraguro, provincia de Loja. - Cabrera Ramon, Marlo Estuardo (2018)
This researchworkentitled THE RECREATIONAL PHYSICAL ACTIVITIES AND THE QUALITY OF LIFE OF THE ELDERLY ADULT, URDANETA PARISH, SARAGURO CANTON, PROVINCE OF LOJA. The research is qualitative, type of longitudinal study, experimental design. It focuses on knowing and helping in a direct way the lifestyle that the older adult has in the field. Its objective is to determine if the practice of physical and recreational activities in the Parroquia Urdaneta, Cantón Saraguro, Provincia de Loja, improves the quality of life. To carry out a data survey, a survey was conducted for the candidates and for their validation the comparison tables of the initial survey and the final of the survey were made, where the final survey showed us that our objective was fully met. It was concluded that in the Barrio Baber, Parroquia de Urdaneta, older adults took care of areas dedicated to them, thus taking care of physical activity, due to work and sedentary lifestyle. A good percentage had noncommunicable diseases. Suggest that they have friends programs for the team in which the main participants are, and carry out that kind of life according to their age.